2009 Information and Communications for Development : Extending Reach and Increasing Impact - World Bank (World Bank, 2012)
The information and communication technology (ICT) is transforming interactions between people, governments, and firms worldwide. In developing countries, farmers receive updated crop prices and public health officials monitor medical inventories by text messages. Women are empowered to make decisions and access new opportunities through online information. Entrepreneurs obtain business licenses in a fraction of the standard time by applying for them through municipal government web sites. And in an increasingly integrated global economy, ICT enables people to access and share knowledge and services around the world. The first report, Information and Communications for Development (IC4D) 2006: global trends and policies, analyzed lessons on developing access to ICT, examined the roles of the public and private sectors in this process, and identified the benefits and challenges of adopting and expanding ICT use in businesses. This second report, IC4D 2009: extending reach and increasing impact, takes a close look at mobile and broadband connectivity. It analyzes the development impact of high-speed Internet access in developing countries and provides policy options for rolling out broadband networks and addressing the opportunities and challenges of convergence between telecommunications, media, and computing. The report also presents a framework of e-government applications and discusses various country experiences with the institutional and policy arrangements for e-government and for the development of the local information technology (IT) and IT-enabled services (ITES) industries. The common thread running through these topics is the development impact of ICT. Finally, the report presents summary tables on ICT sector indicators in 150 economies and introduces new performance measures in terms of access, affordability, and ICT adoption in government and business.